2003
DOI: 10.1016/s1201-9712(03)90044-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an intervention to improve treatment-seeking behavior and prevent sexually transmitted diseases among Nigerian youths

Abstract: Significant improvements in treatment-seeking for STD symptoms can be effected among Nigerian youths. The prevalence of reported STD symptoms can be decreased by improving treatment-seeking for and awareness of STDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(98 citation statements)
references
References 10 publications
3
94
0
1
Order By: Relevance
“…In five of the articles included in the review, condom use increased significantly among males but not females within the same study, 30 31 43 44 49 while only one study found the reverse among youths. 47 This highlights that condom use depends on male cooperation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In five of the articles included in the review, condom use increased significantly among males but not females within the same study, 30 31 43 44 49 while only one study found the reverse among youths. 47 This highlights that condom use depends on male cooperation.…”
Section: Discussionmentioning
confidence: 99%
“…27 43-45 48 The greatest postintervention condom use (78% use in last sex) was reported in an individual-RCT among secondary school students in Namibia who had received HIV/AIDS education, and training in communication and decision-making skills. 27 Otherwise, a cluster-RCT observed a significant difference in ''some'' condom use at follow-up (39% vs 32%), 47 and two other studies reported high levels of ''ever use'' (97% and 55% postintervention). 29 74 Partner type is aggregated or unspecified Twenty intervention studies combined partnership types or did not specify the type of partnership in which condoms were used.…”
Section: Adolescent and Youth Sexmentioning
confidence: 99%
“…In Edo state, the Women's Health and Action Research Centre (WHARC) has also contributed significantly to improving ASRH by conducting research into adolescent health and health seeking behaviour. Significant among their activities was an intervention to improve treatment-seeking behaviour and prevention of STIs among adolescents in Edo state 37 . In Delta state, the Public Health Impact Research Centre (PHIRC), Asaba is another NGO involved in promoting ASRH.…”
Section: Initiatives and Programmes On Asrh By International And Locamentioning
confidence: 99%
“…In-school interventions benefit from a ready-made audience and there is reasonably strong evidence of the benefits of using curriculumbased participatory and life skills approaches to increase knowledge and awareness [19]. Significant increase in condom use, knowledge of STDs and reduction in sexually transmitted disease symptoms as a result of Inschool interventions has been reported in Nigeria when active referral systems between schools and health facilities were evaluated using a Randomized Controlled Trial (RCT) [21]. Earlier evidence of a quasi-experimental evaluation of an out-of-facility based intervention using a matched control did not establish any significant impact on reproductive health service use [22].…”
Section: Introductionmentioning
confidence: 99%